FACTORS INFLUENCING ACCOUNTING STUDENTS’ UNDERSTANDING THE ENGLISH TERMINOLOGY IN ACCOUNTING REPORTS - wurayaningrum, rica s (Prodi Akuntansi FEB UNITOMO, 2021)
This qualitative study with a case study research scheme is aimed to find out the factors influencing accounting students’ understanding of the English terminology in accounting reports (balance sheet, income statement and cash flow statement). The sample is the first semester students of the Accounting Department of Faculty Economics and Business, Universitas Wijaya Kusuma Surabaya academic year 2020-2021. The understanding of English terminology in accounting reports can help the students in preparing themselves for Free Trade in a disruptive era. The analysis of this study is using qualitative descriptive analysis. The results of the study are the description of the factors influencing accounting students’ understanding of the English terminology in accounting reports as for the first semester students this specific terminology may cause confusion which leads to misunderstanding.